Clinical factors associated with functional outcomes in patients with single subcortical infarction with neurological deterioration - Yang, Yi; He, Yue; Han, Wei; Xu, JianHui; Cai, ZhiRong; Zhao, Tian; Shao, YuanWei; Yu, Ming (Frontiers in Neurology, 2023)
Objective: The factors that determine poor outcome in patients with single subcortical infarction (SSI) and in an SSI subgroup with neurological deterioration (ND) may not be identical. This study aims to investigate the effect of ND on the functional outcome of patients with SSI and which clinical factors determine poor outcome in patients with SSI with ND (SSI-ND) and in all SSI patients. Methods: Patients with SSI were consecutively enrolled. ND referred to an increase in the total National Institute of Health Stroke Scale (NIHSS) score ≥ 2 points, an increase in the NIHSS subscore of consciousness or motor function ≥ 1 point, or any new neurological deficit. Results: A total of 255 patients were enrolled, and 9 (3.53%) were lost to follow-up. ND [adjusted relative risk (aRR) = 1.37, 95% confidence interval (CI) = 1.22–1.55, p < 0.001], female sex (aRR = 1.13, 95% CI = 1.03–1.24, p = 0.12), initial NIHSS (aRR = 1.08, 95% CI = 1.07–1.10, p < 0.001), and parent artery disease (PAD) (aRR= 1.16, 95% CI = 1.07–1.26, p = 0.038) were associated with 90-day poor outcome (modified Rankin Scale > 2 points) in patients with SSI. In the SSI-ND subgroup, PAD (aRR = 2.15, 95% CI = 1.20–3.86, p = 0.01), glycosylated hemoglobin (aRR = 1.17, 95% CI = 1.01–1.35, p = 0.035) and severe NIHSS (aRR= 1.15, 95% CI = 1.06–1.25, p = 0.001) predicted poor outcome, and PAD (aRR = 1.87, 95% CI = 1.19–2.95, p = 0.007) correlated with higher worsened NIHSS [> 2 points (median)]. In predicting poor outcome of patients with SSI-ND with PAD, the severest NIHSS (aRR= 1.09, 95% CI = 1.02–1.17, p = 0.01) was the sole determiner, with a cutoff value of 4.5 points; sensitivity and specificity were 94.0% and 83.3%, respectively. Conclusions: ND is an independent predictor of poor outcome in patients with SSI, and poor outcome determiners are not identical in the SSI-ND subgroup and all SSI patients. For patients with SSI-ND, PAD could aggravate ND and hence is an essential predictor of poor outcome.